RESTOTATIVE JUSTICE POLICY OF CLASS I DRUG CONVICTS OF MARIJUANA IN DEALING WITH OVER-CAPACITY CORRECTIONAL INSTITUTIONS IN INDONESIA - Risano, Alfredo; Ningtias, Ayu Dian; Yurita, Rosnia (Jurnal Independent, 2021)
ABSTRACT Law Number 35 of 2009 based on Pancasila and the 1945 Constitution of the Republic of Indonesia, was implemented based on justice, protection, humanity, order, protection and security. Often the authority to try becomes a dilemma for judges when there is a conflict between certainty and a sense of community justice. So it is predictable that the high number of narcotics users greatly affects the number of prisoners/inmates of narcotics abuse cases who enter prisons/detention centers, even though the best place they need is a rehabilitation center. The government, law enforcement officers and the media always provide information about marijuana abuse, if there is abuse the public should also be given information about the 'justification' of marijuana. Here, political will is needed from the government to review policies and provide objective facts about the benefits and dangers of cannabis plants, because politically this can reduce public trust in the government. Based on the facts and explanations of the above, the researchers are interested in conducting legal research on "Restorative Justice for convicts of narcotics users Golonga1 marijuana